281 The Relationship between Postnatal Hormone Concentrations and the Development of Boar Taint at Puberty. (21st September 2022) - Bone, Christine; Squires, E James
Abstract: The development of boar taint is dependent on the balance between the rate of androstenone synthesis and metabolism, which regulates the quantity of androstenone available for accumulation in the fat. The pubertal production of androstenone and other sex steroids is influenced by sexual maturity status and preceded by a significant period of hormone production during postnatal development that occurs from 14 to 35 days of age (DOA). However, the relationship between postnatal and pubertal hormone production is not well understood. Therefore, the purpose of this study was to determine if postnatal hormone concentrations can be used to predict sexual maturity status and boar taint development at puberty. Crossbred [(Yorkshire x Landrace) x Duroc] boars (n=90)] were housed in groups of 10. Blood samples were taken at 14, 21, 28, and 35 DOA and again at 120, 130, and 140kg live weights (LWs) along with backfat samples. Plasma and fat androstenone concentrations were quantified using an androstenone-specific ELISA. Plasma estrone sulfate (E1 S) concentrations were determined by RIA and used as an indicator of sexual maturity status. Statistical analysis was performed using Spearman correlation. Several nonlinear monotonic relationships were identified between postnatal and pubertal hormone concentrations and are presented in Table 1. A moderate positive correlation was identified between plasma androstenone concentrations at 21 and 28 DOA and fat androstenone concentrations at 120, 130, and 140kg LWs, and between E1 S concentrations at 21 DOA and E1 S concentrations at 120, 130, 140kg LWs. However, the strength of the relationship between postnatal and pubertal hormone concentrations was insufficient for accurately predicting sexual maturity status or boar taint at puberty. These results suggest that additional factors regulating the development of boar taint, such as the rate of metabolism or accumulation, should be considered in future efforts to develop a predictive model using postnatal hormone concentrations.